Erosion of a right ventricular pacer lead into the left chest wall - Michael J. Herr; J. Macy Cottrell; H. Edward Garrett Jr.; Darryl S. Weiman (Surgical Case Reports, 2020)
Abstract Background Erosion of a pacer lead into the chest wall may result in pericardial effusion with cardiac tamponade. Free rupture into the pleura or mediastinum can result in hypotension and cardiac arrest. Case presentation We report a unique case of a right ventricular pacer lead which eroded through the right ventricle into the left chest wall and penetrated a rib. The patient presented with a tender chest wall mass without pericardial or pleural effusion. The segment of rib which the pacing lead had penetrated was removed. Conclusions The patient tolerated the procedure well and was discharged 1 week after the operation. This case adds to the current literature the justification of removal of temporary and non-functional pacing leads.